ENVIRONMENTAL APPROACH TO PHYSICAL EDUCATION OF UNIVERSITY STUDENTS - I. V. Manzheley (Образование и наука)
The paper discusses the physical education problems in the context of environmental degradation, uncertainty of socio-economic situation and ideological setting, informational boom, wide spread of the alcohol and drug abuse, etc. As a solution to the problem, the author recommends to propagate the sport lifestyle to university students by creating the proper sports environment; the factors determining the given life style being emphasized, the definition of the university sports environment, its structure and functional system demonstrated. The author describes the theoretical and applied aspects of the environmental approach to physical education based on the constructive interaction and cooperation of teachers and students. The paper considers the sports activity – a semantic core of the approach in question – in terms of the specific sport facilities, behavior regulating rules, and students’ free choice of sport, place and schedules. The conceptual basis of the given approach incorporates the ideas of developmental education and complies with the Federal State Educational Standards. In conclusion, the author demonstrates the changing dynamics of students’ motivation for the mass sports activity resulted from implementation of the environmental approach to physical education at Tumen State University.